Evaluation of TNF-alpha gene (G308A) and MBL2 gene codon 54 polymorphisms in Turkish patients with tuberculosis - Esma Ceylan; Mutlu Karkucak; Hikmet Coban; Mehmet Karadag; Tahsin Yakut (Elsevier, 2017)
Objective: MBL acts as a binding protein that enables uptake of mycobacteria into macrophages. And, TNF-alpha is an important cytokine that is involved in control of mycobacterial infections both in-vivo and in-vitro. A large number of genetic factors exerting susceptibility to tuberculosis has been identified, among which mannose-binding lectin and tumor necrosis factor-alpha call attention. The objective of this study is to compare the frequency of TNF-alpha and MBL gene polymorphisms between patients diagnosed with tuberculosis and healthy volunteers in Turkey, and determine the association between tuberculosis and TNF-alpha gene (G308A) and MBL2 gene codon 54 polymorphisms. Material and methods: The study included 69 patients who were diagnosed with tuberculosis and 70 control subjects. The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method was used to detect TNF-alpha (G308A) gene and MBL2 gene codon 54 polymorphisms. For statistical analysis, the significance level was determined as p < 0.05. Results: A comparison between patient and control groups in TNF-alpha (G308A) gene and MBL2 gene codon 54 polymorphisms showed no statistically significant difference (p > 0.05). However, a comparison of mean body mass index (BMI) and smoking status showed a statistically significant difference between the tuberculosis and control groups (p = 0.01 and p = 0.009, respectively). Conclusion: Our results suggest that the MBL2 gene Codon 54 and TNF-alpha gene G308A polymorphisms are not associated with an increased risk for development of tuberculosis in our patients. Further studies are required including more cases of tuberculosis patients and other potentially relevant gene polymorphisms. Keywords: Tuberculosis, Gene polymorphism, Mannose-binding lectin, Tumor necrosis factor-alpha